β-arrestins - Scaffolds and signalling elements essential for WNT/Frizzled signalling pathways? - Schulte, Gunnar; Schambony, Alexandra; Bryja, Vitezslav (British Journal of Pharmacology, 2010)
β-arrestins were originally identified as negative regulators of G protein-coupled receptor signalling. Recent studies have revealed that β-arrestins serve as intracellular scaffolds and signalling intermediates. Their diverse functions in intracellular signalling pathways provide mechanisms for achieving signal specificity that might be attacked for pharmacological intervention. Here, we summarize the importance of β-arrestin function for WNT [wingless (from Drosophila) and the oncogene int-1]/Frizzled (FZD) signalling. WNTs are secreted lipoglycoproteins that act through the seven transmembrane-spanning receptors of the FZD family. It recently became evident that β-arrestins are required for cellular communication by means of WNTs and FZDs both in cellular systems and in vivo. Although the overall importance of arrestin for WNT/FZD signalling remains obscure, interaction with the central phosphoprotein Dishevelled and the endocytic machinery implicates β-arrestin as a determinant of WNT signalling specificity, a mediator of WNT/FZD desensitization and a regulator of signalling compartmentation. © 2009 The Authors.
Keywords: β-catenin; Canonical signalling; Casein kinase; Desensitization; Dishevelled; Endocytosis; Internalization; Non-canonical signalling; ROR; RYK